THE EFFECTIVENESS OF DISTANCE LEARNING - Dosmyrza, L. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The purpose of this article is to evaluate the effectiveness distance teaching. In this aricle definitions of the distance teaching and an important role of distance learning in education are given. Moreoverthere are different approaches to assessing the effectiveness of different training systems.
Keywords: distance teaching; method; education system; technology